2000
DOI: 10.1590/s0066-782x2000000800005
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characteristics of rat hearts with and without myocardial infarct. Initial experience with doppler echocardiography

Abstract: Objective -To assess by Doppler echocardiography the structural and functional alterations of rat heart with surgical induced extensive myocardial infarction. Methods -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
17
0
3
Order By: Relevance
“…Induction of MI followed a well-established protocol [20][21][22][23][24] . Briefly, after intraperitoneal anesthesia (ketamine 50 mg/kg and xylazine 20 mg/kg), intubation and mechanical ventilation (Harvard Rodent Ventilator, Model 863, Harvard Apparatus, Holliston, MA), thoracotomy was performed in the left hemithorax of each animal.…”
Section: Surgical Induction Of Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of MI followed a well-established protocol [20][21][22][23][24] . Briefly, after intraperitoneal anesthesia (ketamine 50 mg/kg and xylazine 20 mg/kg), intubation and mechanical ventilation (Harvard Rodent Ventilator, Model 863, Harvard Apparatus, Holliston, MA), thoracotomy was performed in the left hemithorax of each animal.…”
Section: Surgical Induction Of Myocardial Infarctionmentioning
confidence: 99%
“…The procedures were performed by an observer blinded to the groups to which the animals had been assigned. A Sonos 5500 equipment (Philips Medical Systems, Andover, MA, USA) with a 12 -MHz transducer was used in a depth between 2 and 3 cm according to previously described methodology 20 . After having their thorax shaved, the animals were placed in the left lateral position.…”
Section: Doppler Echocardiographymentioning
confidence: 99%
“…Although it identifies the presence of an MI-dependent electrically inactive area, the ECG is not a method that can quantify the infarction area 2 . The echocardiogram can determine the presence and the size of the MI with very good sensitivity [3][4][5][6][7][8][9][10][11][12][13][14][15] , even in periods as early as two days after necrosis, and it also provides information about deviant atrial and ventricular function. The best method for post-mortem diagnosis of MI depends on the stage in which the autopsy occurs.…”
mentioning
confidence: 99%
“…The electrocardiogram 2 and the echocardiogram [3][4][5][6][7][8][9][10][11][12][13][14][15] are noninvasive methods capable of identifying the area of necrosis or scarring. Although it identifies the presence of an MI-dependent electrically inactive area, the ECG is not a method that can quantify the infarction area 2 .…”
mentioning
confidence: 99%
“…This instrument has also been used consistently in the ABC for monitoring the process of cardiac remodeling secondary to various stimuli, particularly after experimental acute myocardial infarction 20,21 . Initially, the Doppler echocardiogram presented high sensitivity and specificity for the detection of large infarcts in the chronic phase and identified signs of increased ventricular cavity and pulmonary artery pressure 22 . Subsequently, it was shown that animals subjected to myocardial infarction presented two patterns of left ventricular geometry which were not factors predictive of ventricular dysfunction 23 .…”
mentioning
confidence: 99%